Forest Floor Lead Changes from 1980 to 2011 and Subsequent Accumulation in the Mineral Soil across the Northeastern United States. Issue 3 (1st May 2014) - Richardson, J. B.; Friedland, A. J.; Kaste, J. M.; Jackson, B. P.
Abstract : Quantifying the transport rate of anthropogenic lead (Pb) in forest soils is essential for predicting air pollution impacts on northeastern United States soil quality. In 2011, we resampled the forest floor at 16 sites across the northeastern United States previously sampled in 1980, 1990, and 2002 and also sampled the upper two mineral soil horizons. The mean forest floor Pb concentration decreased from 151 ± 29 mg kg −1 in 1980 to 68 ± 13 mg kg −1 in 2011. However, the mean forest floor Pb amount per unit area remained similar (10 ± 2 kg ha −1 in 1980 and 11 ± 4 kg ha −1 in 2011). Study sites were divided into three geographic regions: western, central, and northern. The modeled forest floor Pb response time (1/ k ) was longer at frigid soil temperature regime sites (61 ± 15 yr) compared with mesic sites (29 ± 4 yr). Mineral soil Pb concentration and amount were approximately four times greater at western and central sites compared with northern sites for both mineral horizons. Furthermore, mean isotope ratios of 206 Pb/ 207 Pb (1.201 ± 0.006) and 208 Pb/ 206 Pb (2.060 ± 0.021) indicated that Pb in the western and central forest floor and mineral soil was primarily gasoline derived. Our combined analytical approach using long‐term forest floor monitoring and stable Pb isotopes suggest that the majority of anthropogenic Pb deposited on soils in the western and central sites has been transported to the mineral soil, whereas it continues to reside in the forest floor at northern sites.